THE TOURISM POTENTIAL AND EFFECTIVE MANAGEMENT OF RURAL HERITAGE ASSETS THROUGH THEME ROUTES - Tibor Gonda; Monika Pentz (Economic Review, 2023)
Hungary’s rich rural heritage values include traditional local products, handicrafts, terroir products, “Hungaricums”. However, these products are not only about preserving values and exploiting them for economic purposes, but also about adding high intellectual capital, community collaboration or environmental awareness raising, social responsibility or even education for sustainability. These key issues can be further enhanced by theme routes based on local heritage values. The development of heritage in tourism is also increasingly becoming an economic interest. The past, which cannot be erased from human memory, is also a resource that is constantly renewed. The development of tourism is one of the dimensions of better exploitation of the natural, historical, cultural, architectural, economic and agricultural heritage accumulated in the Carpathian Basin, as well as of the economic capacity to produce local products. The development of theme  routes is a good practice which has proved successful in several places. In recent years, the process of value creation has involved, and in many cases coordinated, the activities of local communities. Experience both at home and abroad has shown that the exploitation of local values in the community and in tourism has led to a number of good practices, regeneration of communities, and  development of the local economy.